2017
DOI: 10.1136/bmjopen-2017-016676
|View full text |Cite|
|
Sign up to set email alerts
|

Patient preferences for venous thromboembolism prophylaxis after injury: a discrete choice experiment

Abstract: ObjectiveLimited evidence for the optimal venous thromboembolism (VTE) prophylaxis regimen in orthopaedic trauma leads to variability in regimens. We sought to delineate patient preferences towards cost, complication profile, and administration route (oral tablet vs. subcutaneous injection).DesignDiscrete choice experiment (DCE).SettingLevel 1 trauma center in Baltimore, USA.Participants232 adult trauma patients (mean age 47.9 years) with pelvic or acetabular fractures or operative extremity fractures.Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 33 publications
1
43
1
2
Order By: Relevance
“…27,28 Lloyd et al, 31 Locadia et al, 32 Marvig et al, 34 Utne et al 37 27,28 Lloyd et al, 31 Locadia et al, 32 Marvig et al, 34 Tavoly et al, 36 Utne et al 37 ) Range across studies: 0. Gastrointestinal tract bleeding event (Hogg et al, 27 Lloyd et al, 31 Studies assessing the RIOs that medical and surgical patients place on VTE prophylaxis benefits and adverse events showed that VTE risk reduction is a more important factor influencing their preferences than the potential harms of the treatment (510 participants from 3 studies; high certainty) 38,49,56 ( Table 3). The same was true for patients treated for VTE, who held greater concerns for recurrent VTE risk (519 participants from 1 study; moderate certainty).…”
Section: Nonutility Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…27,28 Lloyd et al, 31 Locadia et al, 32 Marvig et al, 34 Utne et al 37 27,28 Lloyd et al, 31 Locadia et al, 32 Marvig et al, 34 Tavoly et al, 36 Utne et al 37 ) Range across studies: 0. Gastrointestinal tract bleeding event (Hogg et al, 27 Lloyd et al, 31 Studies assessing the RIOs that medical and surgical patients place on VTE prophylaxis benefits and adverse events showed that VTE risk reduction is a more important factor influencing their preferences than the potential harms of the treatment (510 participants from 3 studies; high certainty) 38,49,56 ( Table 3). The same was true for patients treated for VTE, who held greater concerns for recurrent VTE risk (519 participants from 1 study; moderate certainty).…”
Section: Nonutility Resultsmentioning
confidence: 99%
“…†Imprecision due to small sample size. 49 Quante et al, 56 Westrich et al 38 ) Patients highly value the benefits of VTE risk reduction of VTE prophylaxis. Preferences changed in favor of subcutaneous injections with an absolute risk reduction of only 1.27% in VTE, also with the assumption of a generally better effectivity (47.4% of patients).…”
Section: Nonutility Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Other experiments in other therapeutic areas have reported a preference for SC injection rather than IV delivery: including in ulcerative colitis 29 and rheumatoid arthritis. 30 However, in these and other settings, sometimes patients have the option of oral formulations, which are preferred over SC administration, 29,31…”
Section: Discussionmentioning
confidence: 99%